If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4a + -2(3a + -5) = 3(a + -2) Reorder the terms: 4a + -2(-5 + 3a) = 3(a + -2) 4a + (-5 * -2 + 3a * -2) = 3(a + -2) 4a + (10 + -6a) = 3(a + -2) Reorder the terms: 10 + 4a + -6a = 3(a + -2) Combine like terms: 4a + -6a = -2a 10 + -2a = 3(a + -2) Reorder the terms: 10 + -2a = 3(-2 + a) 10 + -2a = (-2 * 3 + a * 3) 10 + -2a = (-6 + 3a) Solving 10 + -2a = -6 + 3a Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-3a' to each side of the equation. 10 + -2a + -3a = -6 + 3a + -3a Combine like terms: -2a + -3a = -5a 10 + -5a = -6 + 3a + -3a Combine like terms: 3a + -3a = 0 10 + -5a = -6 + 0 10 + -5a = -6 Add '-10' to each side of the equation. 10 + -10 + -5a = -6 + -10 Combine like terms: 10 + -10 = 0 0 + -5a = -6 + -10 -5a = -6 + -10 Combine like terms: -6 + -10 = -16 -5a = -16 Divide each side by '-5'. a = 3.2 Simplifying a = 3.2
| B/2.4=6 | | Z=ln*(5x^2+4y) | | 10x-6=8+2 | | sen(4x)-sen(2x)=0 | | (x+3)(x-2)=5(x+3) | | 4(x-3)+6(x+10)-15=-22 | | 8-2g+5g+3= | | 4(x-3)+6(x+10)-15=-23 | | 3x(3x^2-10x+3)=0 | | -12h=-60 | | 42=144 | | X+y=4z | | 3x^2+18+24= | | 2a+4=12a+6 | | a*a(a-2b)+3b(a*a-4)= | | t+15=20 | | =-4x^3+18x | | 1/3n4 | | -2p+1=5 | | (5x+7)-(3x-1)=22 | | 2x^2-6ix^3-2x^2+(3-4i)x-5i+2=0 | | 2x^2-6ix^3-2x^2+(3-4i)x-5i=0 | | 2x^2+5x+3=15 | | 22x^2+5x+3=15 | | 0.5x+2.49=-.07x+6.69 | | 1=b-13 | | 3cos^2x=7sinx+5 | | X-52=100 | | 7x+9y=107 | | 2-3x=-2-2x | | 8-1/4z=1 | | 3,6*4/0,6*8 |